"What We Are Going to Eat Today, We Are Looking for It Today": Exploring Barriers and Enablers of Optimal Complementary Feeding in Madagascar. (29th May 2020) - Rakotomanana, Hasina; Walters, Christine; Komakech, Joel; Hildebrand, Deana; Gates, Gail; Thomas, David; Stoecker, Barbara
Abstract: Objectives: Complementary feeding practices in Madagascar are inadequate. The purpose of this study was to identify maternal barriers to and enablers of optimal child feeding practices in the Vakinankaratra region of Madagascar. Methods: Seven focus group discussions with mothers ( n = 46) who had a child aged 6–23 months and eight in-depth interviews were conducted with community health workers (6), a nurse (1), and a program field monitor (1) in Malagasy, the local language. Discussions were transcribed verbatim, then back-translated into English. The average length of the interviews was 50 minutes. The translated transcripts from the discussions and interviews were analyzed using NVivo v.12 and a thematic analysis approach was used. Results: Poverty, lack of money, and limited food availability were mentioned by the mothers as obstacles to adequate complementary feeding practices. Lack of time because of work as well as heavy workload also were cited as problems. Mothers generally decide alone on what food to give to their infants, with little to no help from spouse or relatives. All mothers considered their children's health and giving them appropriate complementary foods as important. Another potential enabler was that mothers trust the community health workers and usually ask them for help and/or information on child feeding. The key informants confirmed all of the mothers' responses. Conclusions: Interventions that aim to improve feeding practices in the Vakinankaratra region should address food insecurity and improve households' income. Strengthening the local infrastructures with the community health workers appears to be important when aiming to reinforce appropriate feeding practices. Funding Sources: This study was funded by the Marilynn Thoma Chair in Human Sciences at Oklahoma State University.